Relação entre a Rede Municipal de Ensino e o Terceiro Setor para a escolarização das pessoas com deficiência em Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This research analyzed the relationship between the municipal education network and the Third Sector for the schooling of people with disabilities in Manaus. In order to reach the main objective of the work, we set as specific objectives: To characterize the contemporary debate around the theme of inclusion, public policies, Special Education in the perspective of inclusive education and participation of the Third Sector in the schooling of people with disabilities; Understand the Brazilian State Reform as part of the broader context of globalization of capital, linking it with the Third Sector's performance in the area of Special Education; To discuss, in the light of the international movements and national documents on Special Education in the perspective of inclusive education, the partnership between the municipal teaching network of Manaus and the institutions of the Third Sector; To problematize the mechanisms for monitoring and supervising this partnership, undertaken by the Municipal Department of Education of Manaus - SEMED, with a view to ensuring access, permanence and quality of schooling for people with disabilities. The theoretical basis was supported by Bueno (1993, 1999, 2004, 2011); Kassar (1998, 2011, 2012) and Peroni (2003, 2006, 2008, 2008a, 2011, 2013, 2014 and 2016), as well as the study of master's and doctoral studies of Brazilian postgraduate programs on the subject. Documentary research subsidized data collection, prioritizing legislation and guidance documents at the federal, state and municipal levels that deal with Special Education and public sector partnerships with the Third Sector institutions that work in Special Education; including the Terms of Agreement and other documents that guide the collaboration between the Municipal Department of Education of Manaus - SEMED and the institutions of the Third Sector. As a theoretical-methodological support, we use the dialectical perspective (BROHN, 1979, FRIGOTTO, 2000, 2006 and 2010), based on the strategies of documentary analysis advocated by Ball (1994, 1998, 2004) and his followers as Shiroma (2006, 2008 and 2013) and Mainardes (2006). The results of the research contributed to ratify the thesis that to the extent that school education is not offered exclusively by the State, but also by the private sector, the introduction of the market logic in the promotion of the right to education is moving away from the democratic ideology while a right of all and a duty of the State. Extending the human and material resources of private institutions through agreements with the public power, to the detriment of the demands of the municipal public schools of Manaus that attend students with disabilities. Therefore, the Third Sector, in the area of Special Education in the perspective of inclusive education, is protected by the State.
Keywords: Educação Especial; Políticas Públicas; Educação Inclusiva; Terceiro Setor; Escolarização da Pessoa com Deficiência; CIÊNCIAS HUMANAS: EDUCAÇÃO: TÓPICOS ESPECÍFICOS DE EDUCAÇÃO: EDUCAÇÃO ESPECIAL